Some Results on Nano Perfect Mappings - Mohsin, Estabraq Abd Al-Kareem; Yousif, Yousif Yaqoub; El Sayed, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The structure of this paper includes an introduction to the definition of the nano topological space, which was defined by M. L. Thivagar, who defined the lower approximation of G and the upper approximation of G, as well as defined the boundary region of G and some other important definitions that were mentioned in this paper with giving some theories on this subject. Some examples of defining nano perfect mappings are presented along with some basic theories. Also, some basic definitions were presented that form the focus of this paper, including the definition of nano pseudometrizable space, the definition of nano compactly generated space, and the definition of completely nano para-compact. In this paper, we presented images of nano perfect mappings with some definitions and important evidence related to them, then we presented inverse images of nano perfect mappings with related theories.